2019
DOI: 10.5194/isprs-archives-xlii-2-w18-53-2019
|View full text |Cite
|
Sign up to set email alerts
|

3d Images for Automated Digital Odontometry

Abstract: Abstract. Improvements of existing and development of new non-contact measurement techniques, especially for surfaces of complex spatial shape, allow involvement of various disciplines into advanced technological reality. These improvements have two major directions. The first, being more obvious, refers to introduction of accurate digital 3D images in spheres where real objects have become subjects of traditional study, techniques or manufacturing technologies. The other direction deals with substantial metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…We should also mention that all of the studied upper teeth are wider that the lower molar from Fofanovo, not including its comparable sizes of vestibular cusp (5,65 mm), which is predominantly due to pronounced outer slope (contour length -5,32 mm); however, due to morphology of the masticatory system and orthognathic closure pattern of upper and lower teeth, it is more correct to compare lower vestibular cusps with upper oral. Another significant part of odontometric data referring to this study subject, as well an extension of our previous studies (Gaboutchian et al, 2019), are angular measurements. And here as well we can find support for the observed dental morphology: the sharpest angle among oral cusp belongs to 1.7 C2 (82,8º).…”
Section: Odontometric Datasupporting
confidence: 52%
See 2 more Smart Citations
“…We should also mention that all of the studied upper teeth are wider that the lower molar from Fofanovo, not including its comparable sizes of vestibular cusp (5,65 mm), which is predominantly due to pronounced outer slope (contour length -5,32 mm); however, due to morphology of the masticatory system and orthognathic closure pattern of upper and lower teeth, it is more correct to compare lower vestibular cusps with upper oral. Another significant part of odontometric data referring to this study subject, as well an extension of our previous studies (Gaboutchian et al, 2019), are angular measurements. And here as well we can find support for the observed dental morphology: the sharpest angle among oral cusp belongs to 1.7 C2 (82,8º).…”
Section: Odontometric Datasupporting
confidence: 52%
“…As can be seen, odontological study of the morphological feature has been traditionally held in the nature of descriptive objectivityas non-metric. Previously these teeth have been studied through angular measurement (Gaboutchian et al, 2019), and the parameters were found to be effective for comparisons with teeth not representing this morphological feature. However, more profound measurements can be performed for odontological analysis of trait expression degree in anthropological research through implementing automated digital odontometry.…”
Section: Sunghir': the Problem Of Measuring Dental Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus automated digital odontometry is the other approach to measurements of teeth in the current study, or even not teeth but rather their 3D images. Fully automated algorithms based on morphological interpretations allow orientation, sectioning and measurements of a wide variety of different linear, angular, area parameters as well as calculation of coefficients and parameter ratios (Gaboutchian et al, 2017, Gaboutchian et al, 2019. Landmark setting on 3D surfaces and 2D contours does not require much effort or profound skills in odontometry or anthropology from the operator.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, they are not intended for scanning teeth unless opaque spray is applied (but it is preferable to avoid contamination either in case of intraoral procedures or for scanning palaeoanthropological findings). As an alternative, there are examples of successful application of intraoral scanners which were initially designed for clinical use in dental practice [39][40][41][42].…”
Section: Imaging Techniquesmentioning
confidence: 99%